Factors Associated with Primary Open-angle Glaucoma in a Nepali Population: Jiri Eye Study - Sharma, Archana; Poudel, Manish; Banjara, Pradeep; Shrestha, Mohan Krishna; Thapa, Suman Shumsher (Nepalese Journal of Ophthalmology, 2025)
Introduction: Glaucoma is the second most common cause of blindness with primary open-angle glaucoma (POAG) as one of the leading causes. Objective: To study the ocular and systemic associated factors that lead to the development of primary open-angle glaucoma. Methodology: This is population-based, analytical cross-sectional, oculo-genetic study conducted from 2015 to 2018. Among the total 2042 study participants ≥18 years of age, included using convenience sampling, 37 were diagnosed with POAG. For comparative analysis, age and gender matched controls without glaucoma were selected in a 1:4 ratio from the same population. A detailed systemic and ophthalmic history was recorded; systemic and ophthalmic examinations were carried out. Examinations also included measurement of blood pressure and body mass index. A comprehensive ophthalmic examination included measurement of visual acuity, refraction, slit lamp bio microscopy, recording of intraocular pressure, gonioscopy and dilated fundus examination. Keratometry, biometry, visual field assessment, anterior and posterior segment Optical Coherence Tomography were undertaken. Result: Prevalence of POAG among ≥30 years was 2.53%, (males 0.98%, female 0.83%). The mean IOP was 15.34 (±3.74) mmHg. Those ≥40 years had an increased risk of developing POAG. POAG was associated with increased intraocular pressure (p = 0.019), increased vertical cup disc ratio (p <0.001), retinal nerve fibre layer thinning (p<0.001), increased pattern standard deviation (p <0.001) and decreased mean deviation (p = 0.020). Other factors such as BMI, DM, HTN, family history of glaucoma, smoking, alcohol consumption, tobacco chewing, refractive error, CCT, CCR, ACD, AL, lens thickness, and iris thickness were not associated. Conclusion: Identifying the factors associated with POAG and adopting screening strategies for its early detection will prevent blindness in this population.